2019
DOI: 10.1177/2333721419848153
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Frailty in Primary Care: Feasibility and Acceptability of Recommended Case Finding Tools Within a Primary Care Integrated Seniors’ Program

Abstract: Frailty-a dynamic and multidimensional state of increased vulnerability-often remains undetected in primary care until its late presentation when a seemingly minor event results in significant health crisis (Moody, Lyndon, & Grant, 2017) affecting an individual's level of function and independence (Di Pollina et al., 2017; Landi et al., 2004). Frailty is associated with an aging population, with prevalence rates in Canada of 25% in those 65 years of age up to 50% in those above 80 years (Muscedere et al., 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Moreover, it had the highest acceptability rating for both patients and administering nurses, and was rated first for five of six individual criteria ranked by nurses. These findings for the P7 are consistent with respect to completion rate, skills, equipment, time to complete, space requirements and provider acceptability as a previous study conducted in general practice [26]. Recent research has also indicated that it returns relatively high diagnostic and predictive accuracy in primary care settings [13,[42][43][44], although more replication studies are needed to ensure generalisability.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Moreover, it had the highest acceptability rating for both patients and administering nurses, and was rated first for five of six individual criteria ranked by nurses. These findings for the P7 are consistent with respect to completion rate, skills, equipment, time to complete, space requirements and provider acceptability as a previous study conducted in general practice [26]. Recent research has also indicated that it returns relatively high diagnostic and predictive accuracy in primary care settings [13,[42][43][44], although more replication studies are needed to ensure generalisability.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings lend weight to the viewpoint that rapid frailty screening instruments of the type included within this study are more practical to implement than reference standards within busy general practice settings. It has frequently been asserted within the frailty literature that GPs and their teams need to be able to implement simple, rapid frailty screening due to time constraints [4,12,25,26,42]. Our results show that screening instruments took consistently less time to implement than the reference standards, which in the case of the FP also required physical space and equipment that may not be readily available within most general practice settings.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations